1978
DOI: 10.1111/j.1471-4159.1978.tb07052.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Diversity Studies of Rat Brain Rna: Effects of Environmental Complexity on Rat Brain Rna Diversity

Abstract: Abstract— The sequence complexities of rat brain RNAs were measured by RNA‐driven hybridization reactions with nonrepetitive rat DNA. The total sequence complexity of rat brain HnRNA was estimated to be 6.61 x 108 nucleotides while rat brain poly(A)‐mRNA sequence complexity was 1.32 x 108 nucleotides. Up to 33.7% of the total transcribable nonrepetitive DNA was expressed in the nuclear RNA. The nuclear RNAs reacted with complex kinetics over at least 4.5 decades of equivalent Rot (product of RNA concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(28 citation statements)
references
References 38 publications
(4 reference statements)
2
26
0
Order By: Relevance
“…To further investigate the effect of the normalization procedure on the subset of mitochondrial 16S rRNA clones (1.4%, 1%, and 0.4% in the IB, 1NIB and 2NIB libraries, respectively), we compared the sequences of a number of 16S rRNA clones isolated from both the IB and 1NIB libraries (kindly provided by M. Adams, Institute for Genomic Research and J. Sikela, University of Colorado). This analysis (data not shown) revealed that the 16S rRNA clones isolated from 1NIB did not correspond to (22,23) and also the data of saturation experiments with single-copy genomic DNA tracer (24,25). "The number of different RNA species in each component was estimated from their complexities by assuming that the average size of brain mRNA is 2.7 kb (26).…”
mentioning
confidence: 98%
“…To further investigate the effect of the normalization procedure on the subset of mitochondrial 16S rRNA clones (1.4%, 1%, and 0.4% in the IB, 1NIB and 2NIB libraries, respectively), we compared the sequences of a number of 16S rRNA clones isolated from both the IB and 1NIB libraries (kindly provided by M. Adams, Institute for Genomic Research and J. Sikela, University of Colorado). This analysis (data not shown) revealed that the 16S rRNA clones isolated from 1NIB did not correspond to (22,23) and also the data of saturation experiments with single-copy genomic DNA tracer (24,25). "The number of different RNA species in each component was estimated from their complexities by assuming that the average size of brain mRNA is 2.7 kb (26).…”
mentioning
confidence: 98%
“…Significantly greater diversity of brain RNA has been found in EC than in IC rats in double-blind experiments using unique sequence molecular hybridization (Grouse, Schrier, Bennett, Rosenzweig, & Nelson, 1979). It is tempting to interpret this result as reflecting greater diversity of proteins in the brains of EC than in those of IC rats, but such a conclusion would be premature because of complexities in RNA functions.…”
Section: Effects Of Training and Experience On Brain And Behaviormentioning
confidence: 75%
“…The probe was 67% reactable with mouse total DNA as has been described [181. The extent of hybridization was assayed by S, nuclease digestion of unhybridized DNA as described [16].…”
Section: Methodsmentioning
confidence: 99%